2018
DOI: 10.1111/echo.13841
|View full text |Cite
|
Sign up to set email alerts
|

The role of type 2 diabetes mellitus on hypertensive‐related aortic stiffness

Abstract: Our data suggest that people suffering from both T2DM and hypertension have more impaired aortic elastic properties than those hypertensive alone. Considering the prognostic role of aortic stiffness, these patients may benefit from a closer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Sciatti et al. 20 suggested that people suffering from T2DM and hypertension have more impaired aortic elastic properties than those with hypertensive alone. Non-enzymatic glycosylation of proteins in the arterial wall in the course of chronic hyperglycemia is associated with functional and structural changes within the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatti et al. 20 suggested that people suffering from T2DM and hypertension have more impaired aortic elastic properties than those with hypertensive alone. Non-enzymatic glycosylation of proteins in the arterial wall in the course of chronic hyperglycemia is associated with functional and structural changes within the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…In the parasternal long-axis view, both systolic and diastolic inner diameters of the ascending aorta were measured via M-mode echocardiography 3 cm above the aortic annulus 11. Three measurements were obtained from 3 consecutive cardiac cycles and the mean values of aortic systolic diameter (AoSD) and aortic diastolic diameter (AoDD) were calculated 11. ASI was calculated by following formula:11,12…”
Section: Methodsmentioning
confidence: 99%
“…Three measurements were obtained from 3 consecutive cardiac cycles and the mean values of aortic systolic diameter (AoSD) and aortic diastolic diameter (AoDD) were calculated 11. ASI was calculated by following formula:11,12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 diabetes mellitus (T2DM), a glucose-, lipid-, proteinand water-electrolyte metabolic disorder, risks micro-and macrovascular damage (1). T2DM is associated with various chronic complications, which may result in high rates of disability and mortality (2).…”
Section: Introductionmentioning
confidence: 99%